PEDAGOGICAL OPPORTUNITIES FOR THE UPBRINGING OF PHYSICAL QUALITIES BY PURPOSEFUL DEVELOPMENT OF ACTION POTENTIAL IN PRESCHOOL CHILDREN - Achilova Saxibakhon Khamidovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
One of the most important tools in the upbringing of a healthy child is physical exercise, moving games, and sports entertainment. When performing physical exercises with children, it is very important to monitor their health, and pay attention to their appearance, mood, fatigue, appetite, and posture. It is desirable that every even absolutely healthy child has a medical examination 2-3 times a year. Development of the necessary and sufficient level of development of physical qualities, movement skills, and skills of the child in accordance with the nature and individual - appropriate way, giving information on physical general education to children of preschool age, achieving the assimilation of intellectual, technological, moral, ethical and aesthetic values related to their physical education, the relevance of knowledge at the level of initial skills.